FEASIBILITY OF PICTURE STORYBOOK FOR READING COMPREHENSION IN ELEMENTARY SCHOOL - Amah, Sri; Hendratno; Istiq'faroh, Nurul (Universitas Muhammadiyah Makassar, 2026)
Despite growing recognition of the importance of contextual literacy media, there remains a significant gap in the availability of culturally grounded picture storybooks tailored to students in newly developed regions such as the Nusantara Capital City (IKN) area. This study aims to analyze the feasibility of the picture storybook “Langkah Kecil Eka di Ibu Kota Nusantara” as a learning medium to improve reading comprehension skills among fourth-grade elementary school students. A qualitative descriptive method was employed. Data were collected through passive participatory observation, in-depth interviews with nine participants (two fourth-grade teachers, one school principal, and six fourth-grade students), and documentation at SD Negeri 006 Sepaku, Sepaku District, North Penajam Paser Regency. Analysis was conducted systematically on four components content/material, language, illustration, and curriculum alignment using the interactive analysis model of Miles, Huberman, and Saldaña (2014), with data validity ensured through source and technical triangulation. The findings indicate that the book demonstrates high alignment with the Indonesian Language Learning Achievement for Phase B in the Merdeka Curriculum, incorporates contextual local wisdom values of IKN, and presents illustrations that support students’ inferential comprehension. This study contributes an evidence-based feasibility analysis of a locally situated literacy medium, offering a replicable framework for developing culturally responsive reading materials in under-resourced and newly established educational contexts across Indonesia.